UJI UNJUK KERJA MESIN PEMBELAH DAN PEMERAS JERUK MANIS (Citrus x sinensis) - Anang Supriadi Saleh; Yossi Wibisono; Zaenal Abidin (JURNAL AGROTEKNOLOGI, 2021)
The process of sweet oranges (Citrus x sinensis) into orange fruit juice gives benefits for the community because at the harvest time, sweet orange fruit prices fell and people can sell as fresh orange juice or as raw material for processing drinks. People still struggle with cheap squeezing machines. This research was a continuation of previous research with the title design of an orange juice extract machine for small-scale industries. This machine was made at a low price, made from local materials, easy to maintain, and can be applied for sweet orange farmers and small-scale industries. The aim of this research was to perform performance tests for sweet orange stripping and squeezing machine. The research method in this machine testing used a combination of big size Semboro sweet orange (Ø 65 mm), small size Semboro orange (Ø 49 mm), peeled orange, and orange not peeled. Each combination of treatment uses 16 kg of sweet orange fruit and was repeated three times, then the extraction yield and extortion work capacity were calculated. The results of testing the extracts of sweet orange fruit extracts showed that the testing of big size sweet oranges (Ø 65 mm) without peeling resulted in fruit juice yield of 33.8%, with a working capacity of 167.3 kg/hour. Keywords: performance tests, small scale industry, sweet orange, work capacity